Use of a mobile device app: a potential new tool for poster presentations and surgical education. (June 2013) - Atherton, S; Javed, M; Webster, SV; Hemington-Gorse, S
<x xml:space="preserve">Abstract</x> Introduction: Poster presentations are an important part of presenting scientific techniques and represent an integral part of conferences and meetings. Traditionally, paper format is used; however, in recent years electronic posters and other methods, such as incorporating a DVD player as part of a poster, have been successfully used. We describe and demonstrate the use of an augmented reality application for smartphones and tablets as a potential future addition to the presentation of scientific work and surgical techniques in poster format. This method allows the audience to view surgical techniques and research as 3D animation or video by using a trigger image in a poster/journal/text book via their smart device. Method: The author used the free Aurasma© application available on both iOS and Android 2.2 and higher platforms from iTunes App Store and Google Play. Once installed, any user with a 3G or WiFi connection via a smart phone or tablet can subscribe to the Medical Illustration channel for free. The user can then scan the trigger image placed on a poster with a mobile device to view videos, animations or 3D data. Further interaction can direct the user to a website for more content. Result: The author has trialled this method at a regional burns and plastic surgery centre and found it to be highly effective. Conclusion: The use of this novel method adds a new dimension to the presentation of scientific work at surgical and medical conferences and as part of journals and textbooks by permitting users to view scientific data and techniques on mobile devices as videos or as three dimensional environments at their own leisure.